Clinico pathological study of Odontogenic cysts and tumors in a Tertiary care Dental hospital of Nepal - Bajracharya, Dipshikha; Ojha , Bidhata; Koju, Sushmit; Maharjan, Nisha (Journal of Kathmandu Medical College, 2022)
Background: Diagnosis of odontogenic cysts and tumours requires detailed clinical, radiographical, and histopathological findings. Fourth edition WHO 2017, classification of Head and Neck lesions, reclassified odontogenic cysts and tumours. Objectives: To know relative frequency of odontogenic cysts and tumours according to WHO 2017 classification and to know their clinico-pathological characteristics in selected population of Nepal. Methods: An analytical cross-sectional study was done in 163 biopsies. Data were obtained conveniently from records of patients diagnosed with odontogenic cysts and tumours from April 2014-2021. Cases with complete clinical details were included whereas non-odontogenic cysts, oral soft tissue, and salivary gland lesions were excluded. Reclassification according to WHO 2017 classification was done. Age, gender, site, clinical presentations, and histological type were analysed using SPSS v.21. Results: In total of 163 biopsies, 120 (73.62%) cases were of odontogenic cysts and 43 (26.38%) cases were of odontogenic tumours. The mean age of occurrence for cysts was 33.35 ± 16.67 years and for tumours was 28.91 ± 13.96 years. Radicular cyst (49/120, 40.83%) and conventional ameloblastoma (23/43 53.48%) were the commonest cysts and tumours. Male (67/120, 55.83%) and female (24/43, 55.81%) predisposition was seen in cysts and tumours. Mandibular middle and posterior region were commonly affected in both cysts (58/162, 35.8%) and tumours (38/53, 71.7%). Conclusion: Increased frequency of radicular cysts and conventional ameloblastoma were appreciated with male predisposition in tumours and female predisposition in cysts. Both cysts and tumours were common in second to third decade of life affecting middle and posterior region of mandible.